Marine systematic conservation planning for Rodrigues Island, western Indian Ocean. (October 2016) - Pasnin, Olivier; Attwood, Colin; Klaus, Rebecca
Abstract: There is a growing number of Marine Protected Areas (MPAs) that have been selected and designed through participatory processes, following the recognition of the need to increase the involvement of local communities likely to be affected by such developments. In parallel with this shift has been the development of systematic conservation planning (SCP) tools that have increased our capacity to design MPAs to maximise biodiversity outcomes and to scale-up community-based initiatives into more comprehensive MPA networks. In Rodrigues, four Marine Reserves (no-take zones) in the north of the island were identified through participatory processes. A Marine Protected Area (multi-use), South East Marine Protected Area (SEMPA), has also been gazetted in the south of the island through a community-based approach. In order to verify and assess gaps in the stakeholder-based design, a Marine Reserve network was designed using the SCP tool Marxan using available spatial data on marine biotopes and fishing effort (FE) to achieve fisheries benefits and marine biodiversity protection. The Marxan analysis identified that only two of the four marine reserves achieve partly the objectives set and SEMPA contains planning units which can be considered as no take zones. This study shows the importance of using both stakeholder's knowledge and scientific input for a better design of MPAs. The results from the analyses can be used by decision makers to inform decisions in a scientific way by providing a set of scenarios from the Marxan analysis.